Ketoconazole as second-line treatment for Cushing’s disease after transsphenoidal surgery: systematic review and meta-analysis - Viecceli, Camila; Mattos, Ana Carolina Viana; Hirakata, Vânia Naomi; Garcia, Sheila Piccoli; Rodrigues, Ticiana da Costa; Czepielewski, Mauro Antônio (Frontiers in Endocrinology, 2023)
The first-line treatment for Cushing's disease is transsphenoidal surgery for pituitary tumor resection. Ketoconazole has been used as a second-line drug, despite limited data on its safety and efficacy for this purpose. The objective of this meta-analysis was to analyze hypercortisolism control in patients who used ketoconazole as a second-line treatment after transsphenoidal surgery, in addition to other clinical and laboratory criteria that could be related to therapeutic response. Methods: We searched for articles that evaluated ketoconazole use in Cushing's disease after transsphenoidal surgery. The search strategies were applied to MEDLINE, EMBASE and SciELO. Independent reviewers assessed study eligibility, quality, and extracted data on hypercortisolism control and related variables, such as therapeutic dose, time, and urinary cortisol levels. Results: After applying the exclusion criteria, 10 articles (1 prospective, 9 retrospective, totaling 270 patients) were included for complete data analysis. We found no publication bias regarding reported biochemical control or without biochemical control (p = 0.06 and p = 0.42 respectively). Of 270 patients, biochemical control of hypercortisolism occurred in 151 (63%, 95% CI 50-74%) and without biochemical control in 61 (20%, 95% CI 10-35%). According to the meta-regression, neither the final dose, treatment duration, nor initial serum cortisol levels were associated with biochemical control of hypercortisolism. Conclusion: Ketoconazole can be considered a safe and efficacious option for Cushing's disease treatment after pituitary surgery. This review was registered in PROSPERO (CRD42022308041).